Outage Constrained Robust Transmission Design for IRS-aided Secure Communications with Direct Communication Links - Hong, Sheng; Pan, Cunhua; Zhou, Gui; Ren, Hong; Wang, Kezhi (IEEE Transactions on Communications, 2023)
This paper considers an intelligent reflecting surface (IRS) aided secure communication with direct communication links where a legitimate receiver (Bob) served by a base station (BS) is overheard by multiple eavesdroppers (Eves), meanwhile the artificial noise (AN) is incorporated to confuse Eves. Since Eves are not legitimate users, their channels cannot be estimated perfectly. We investigate two scenarios with partial channel state information (CSI) error of only cascaded BS-IRS-Eve channel and full CSI errors of both cascaded BS-IRS-Eve channel and direct BS-Eve channel under the statistical CSI error model. To ensure the security performance under CSI errors, the transmit beamforming, AN spatial distribution at the BS, and phase shifts at IRS are jointly optimized to minimize the transmit power constrained by the minimum data rate requirement of Bob and the outage probability of maximum data rate limitation of Eves. In contrast to existing works, the direct link considered in our work makes the optimization of phase shifts at IRS much more challenging, thus we propose a series of novel and artful mathematical manipulations to tackle this issue. Moreover, the proposed algorithm can be applied for both uncorrelated and correlated CSI errors. Simulations confirm the superiority of our proposed algorithm.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Array signal processing; Channel estimation; Covariance matrices; CSI errors; direct communication link; Intelligent Reflecting Surface (IRS); Minimization; MISO communication; Optimization; outage probability; Receivers; robust transmission design; secure communication